Combating Land Degradation in Production Landscapes : Learning from GEF Projects Applying Integrated Approaches - Global Environment Facility (World Bank, Washington, DC, 2014)
During the Fifth Replenishment Phase of the Global Environment Facility (GEF-5), portfolio monitoring and learning review were introduced as key components of knowledge management in the GEF Secretariat. These strategies were intended to address the need to generate knowledge on innovative practices, experiences, and lessons from projects financed by the GEF. In that regard, the Land Degradation focal area strategy for GEF-5 specifically included a learning objective on the catalytic effect of the GEF integrated Approaches, practices focused on integrating the management of land, soil, water, biodiversity, and biomass, in production systems (agriculture, rangelands, and forest landscapes). The focal area strategy embodies the landscape approach and integrated ecosystem management principles to maximize the global environmental benefits of combating land degradation. As a result of that focus, the strategy also addresses the need to harness and safeguard ecosystem services (carbon cycling, biodiversity, hydrological flows, and healthy soils). This report synthesizes the review of the catalytic role of the GEF in promoting integrated approaches in production systems, which are the primary focus of the Land Degradation focal area. The report highlights the context and rationale for GEF financing under OP 12 and OP 15, the catalytic role of GEF financing in promoting integrated approaches, and lessons from the application of integrated approaches to combat land degradation. Because the focus was entirely on learning, this report offers no specific judgments or interpretations about environmental or development impacts of GEF investments. Rather, it highlights the processes, practices, tools, and knowledge innovations embodied in projects that apply integrated approaches.